Iridium Complexes as Efficient Catalysts for Construction of α‐Substituted Ketones via Hydrogen Borrowing of Alcohols in Water. Issue 9 (23rd February 2021) - Luo, Nianhua; Zhong, Yuhong; Wen, Huiling; Shui, Hongling; Luo, Renshi
Abstract: Ketones are of great importance in synthesis, biology, and pharmaceuticals. This paper reports an iridium complexes‐catalyzed cross‐coupling of alcohols via hydrogen borrowing, affording a series of α ‐alkylated ketones in high yield (86 %–95 %) and chemoselectivities (>99 : 1). This methodology has the advantages of low catalyst loading (0.1 mol%) and environmentally benign water as the solvent. Studies have shown the amount of base has a great impact on chemoselectivities. Meanwhile, deuteration experiments show water plays an important role in accelerating the reduction of the unsaturated ketones intermediates. Remarkably, a gram‐scale experiment demonstrates this methodology of iridium‐catalyzed cross‐coupling of alcohols has potential application in the practical synthesis of α ‐alkylated ketones. Abstract : An iridium complexes‐catalyzed cross‐coupling of alcohols via hydrogen borrowing is reported, affording a series of α ‐alkylated ketones in high yield and chemoselectivities. Moreover, this methodology has the advantages of low catalyst loading and environmentally benign water as the solvent. In addition, a gram‐scale experiment demonstrates the potential application in the practical synthesis of α ‐alkylated ketones.